Technological surveillance as a tool for strategic project management - Flórez Gómez, Leidy Yohana; Silva Giraldo, Cesar Augusto; Dugarte, Juan Sebastián; Mejía, Aizar; Cardenas Solano, Leidy Johanna (Universidad Francisco de Paula Santander, 2015)
Within a competitive environment, companies are constantly searching for information which allows them to establish their strategic development plans. Due to this, Technological Surveillanceis conceived, it is developed with the intention of providing support through observation and analysis of the internal and external variables that define the universe of an organization. Taking into account the above, also starting from the versatility that the Technological Surveillance presents, and besides this has the ability to adjust to different environments and contexts, it turns into a strong reason for conducting this article, analyzing its applicability as a tool for the application of a Strategic Project Management, based in the parameters established by PMBOK, observing the considerations for its application from the start, planning, execution, monitoring and control phases; as well as its relevance as a support tool in the development and monitoring of management plans for management, human resources, quality and acquisitions.